Tax morale and optimal taxation - Werner Gueth; Rupert Sausgruber (Center for Economic Studies and ifo Institute (CESifo), 2004)
We study experimentally how taxpayers choose between two tax regimes to fund a public good. The first-best tax regime imposes a general, distortion-free income tax. However, this tax cannot be enforced. The second-best alternative supplements the income tax by a specific commodity tax. This tax cannot be evaded but distorts optimal consumption choices, instead. The result is that a large majority of subjects prefer the general income tax regime. The bulk of votes is consistent with actual payoffs. We isolate tax morale as cause for payoffs above theoretical predictions.
Keywords: H26; H21; C91; 330; optimal taxation; tax evasion; voting; experiments; Optimale Besteuerung; Steuersystem; Steuermoral; Wahlverhalten; Experiment